Proxy climate record for the last 1000 years from Irish blanket peat and a possible link to solar variability - Blackford, J. J.; Chambers, F. M. (Earth and Planetary Science Letters, 1995)
Recent research has shown that ombrotrophic mires can yield a proxy climate signal based on changes in the degree of peat humification [1,2], and that oceanic margin sites show the most sensitive record [3]. We compare humification records for the last 1000 yr from two radiocarbon-dated blanket peat profiles from western Ireland, and show several corresponding periods of climatic fluctuations. Periods favouring reduced peat decomposition, suggestive of wetter and/or cooler climatic conditions, seem to coincide with periods of reduced sunspot activity and atmospheric 14 C anomalies. Whilst climatologists have continued to debate a link between solar variability on a century timescale and climate change, the exact nature of that link remains elusive [4-7]. The results from Ireland demonstrate that data derived from mires could be relevant to the debate as to the extent of solar forcing in natural climatic variability, and the curves shown provide a continuous record to add to previous evidence for the so-called 'Medieval Optimum' and 'Little Ice Age' [8]. The record may imply that, during the past millennium, climatic change at the oceanic margin of the northeast Atlantic largely corresponded to inferred variations in solar output.